2020
DOI: 10.1155/2020/7856318
|View full text |Cite
|
Sign up to set email alerts
|

Allylmethylsulfide, a Sulfur Compound Derived from Garlic, Attenuates Isoproterenol-Induced Cardiac Hypertrophy in Rats

Abstract: Allylmethylsulfide (AMS) is a novel sulfur metabolite found in the garlic-fed serum of humans and animals. In the present study, we have observed that AMS is safe on chronic administration and has a potential antihypertrophic effect. Chronic administration of AMS for 30 days did not cause any significant differences in the body weight, electrocardiogram, food intake, serum biochemical parameters, and histopathology of vital organs. Single-dose pharmacokinetics of AMS suggests that AMS is rapidly metabolized in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…Allyl methyl sulfide (AMS) is one of the important sulfur compounds obtained from garlic, and studies showed that AMS is a major metabolite that is detected in the human breath and plasma [ 28 ]. Our previous study on AMS suggested that chronic administration of AMS is safe in control rats, where the body weight, food, and water intake along with the histopathology of major organs and serum biomarkers remained normal [ 30 ]. Further, the same study showed a beneficial effect of AMS on isoproterenol-induced cardiac fibrosis and dysregulated extracellular matrix (ECM) deposition in the myocardium [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Allyl methyl sulfide (AMS) is one of the important sulfur compounds obtained from garlic, and studies showed that AMS is a major metabolite that is detected in the human breath and plasma [ 28 ]. Our previous study on AMS suggested that chronic administration of AMS is safe in control rats, where the body weight, food, and water intake along with the histopathology of major organs and serum biomarkers remained normal [ 30 ]. Further, the same study showed a beneficial effect of AMS on isoproterenol-induced cardiac fibrosis and dysregulated extracellular matrix (ECM) deposition in the myocardium [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study on AMS suggested that chronic administration of AMS is safe in control rats, where the body weight, food, and water intake along with the histopathology of major organs and serum biomarkers remained normal [ 30 ]. Further, the same study showed a beneficial effect of AMS on isoproterenol-induced cardiac fibrosis and dysregulated extracellular matrix (ECM) deposition in the myocardium [ 30 ]. Also, our recent finding showed a cardioprotective effect of AMS in pressure overload-induced cardiac hypertrophy and heart failure by ameliorating endogenous antioxidants and mitochondrial function [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study further shows that treatment with SG1002 can prevent Hcy-induced hypertrophy in CBS +/- mice and improve cardiac function by reducing MMP activity and TGF-β activation [ 164 ]. Another H 2 S-releasing compound, allyl methyl sulfide, has been shown to attenuate isoproterenol-induced CH in rats by restoring the levels of MMP-2 and -9 as well as diminishing ROS and apoptosis activities [ 165 ]. In addition, a previous study showed that NaHS treatment can efficiently reduce the oxidative stress, apoptosis, and cardiac dysfunction in isoproterenol-induced CH by decreasing the expression of NOX4, caspase-3, and cytochrome c, which are the key players in the cardiac mitochondrial pathway [ 166 ].…”
Section: H 2 S and Cvdsmentioning
confidence: 99%
“…Pathological cardiac hypertrophy is a common pathophysiological process of various cardiovascular diseases, including hypertension, myocardial infarction, and heart failure [ 1 3 ]. It presents as thickening of the ventricular wall and decreased compliance of the ventricular wall [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%